Co-radicalisation of Islamist and Nativist Extremists in Europe: A Social-psychological and Sociological Perspective - Kaya, Ayhan (Journal of Muslims in Europe, 2021)
Abstract A vast amount of social science research has been dedicated to the study of Islamist extremism – in particular, to uncover its psychological and structural drivers. However, the recent revival of extreme-right extremism points to the need to investigate this re-emerging phenomenon. This article highlights some of the characteristics of the extremisation of Islamism in Europe in parallel with the rise of the extremisation of right-wing extremist groups. In doing so, we explore similarities between Islamist and right-wing extremist individuals and groups. The main premise of the article is that a threat-regulation approach fails to understand the role of contextual and structural factors in the political and religious extremisation of individuals. Instead, the article claims that a reciprocal-threat model can better explain extremist violence since it is based on the idea that nativist and Islamist extremist individuals/groups are mutually threatening each other.